EVALUASI SISTEM MITIGASI PENANGANAN BENCANA GEMPABUMI DI KECAMATAN BANTUL PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Indah, Lenni Kartika; Triatmodjo, Bambang; Triatmadja, Radianta (Civil Engineering Forum Teknik Sipil, 2008)
A tectonic earthquake in Bantul Regency, Yogyakarta occurred at the magnitude of 5.9 Richter Scale just before 05.54 p.m. The earthquake duartion was only about one minute but killed thousands of inhabitants, destroyed uncountable number of settlement buildings and damaged other buildings of about billions rupiahs. This fact showed that disaster mitigation system has nott been effective to minimize disaster impact. To absolutely prevent the earthquake disaster to happen is indeed very impossible to do. But humans can seek efforts to take preventive measures to reduce the adverse impact of the earthquake before it occurs again. Therefore, it is necessary to carry out the system of disaster mitigation so that victims and material losses resulted from the earthquake disaster can be minimized. The research objective is to obtain the physical conditions and problems faced by Bantul Regency after the earthquake disaster, to evaluate the exercise of earthquake management, and finally to search solutions in anticipating the occurrence of the earthquake disaster. It is expected that in the future, the response and the willingness of dealing similar disaster can be prepared. A field research is conducted by using three techniques including observation, interview, and questionnaire given to village apparatuses and local society. A bottomup approach is used to ensure that the system to be developed can actually reflect the emergent needs of the community. The result of the research indicates that it is necessary to carry out several alternatives for immediate prevention and comprehensive handling of earthquake disaster by meeting objectives in appropriate strategy of mitigating measure priorities. The first priorities are given to constructing measures or structuring enduring-to-earthquake houses with priorities rank given to forming elements of enduring-to-earthquake building. The first is the frame structures (sloof, column, and block), the roof elements, and the foundation elements, the second is the measures of social aids giving, and the third is the measures of community development with education and training. The fourth is measures of economic development, and, finally, the fifth is the measures of instance and managerial development (early warning system). It is expected that the objectives of the priority strategy can help society to take any appropriate measures in anticipating the risks of earthquake disaster.